Impact of a Daily PICU Rounding Checklist on Urinary Catheter Utilization and Infection - Siegel, Benjamin I. (Pediatr Qual Saf, 2018)
INTRODUCTION: In critically ill children, inappropriate urinary catheter (UC) utilization is associated with increased morbidity, including catheter-associated urinary tract infections (CAUTIs). Checklists are effective for reducing medical errors, but there is little data on their impact on device utilization in pediatric critical care. In this study, we evaluated UC utilization trends and CAUTI rate after implementing a daily rounding checklist. METHODS: A retrospective review of our checklist database from 2006 through 2016 was performed. The study setting was a 36-bed pediatric intensive care unit in a quaternary-care pediatric hospital. Interventions included the “Daily QI Checklist” in 2006, ongoing education regarding device necessity, and a CAUTI prevention bundle in 2013. UC utilization and duration were assessed via auto-correlated time series models and Cochran-Armitage tests for trend. Changes in CAUTI rate were assessed via Poisson regression. RESULTS: UC utilization decreased from 30% of patient-days in 2006 to 18% in 2016 (P < 0.0001, Cochran-Armitage trend test), while duration of UC use (median, 2.0 days; interquartile range, 1–4) did not change over time (P = 0.18). CAUTI rate declined from 9.49/1,000 UC-days in 2009 to 1.04 in 2016 (P = 0.0047). CONCLUSIONS: Implementation of the checklist coincided with a sustained 40% reduction in UC utilization. The trend may be explained by a combination of more appropriate selection of patients for catheterization and improved timeliness of UC discontinuation. We also observed an 89% decline in CAUTI rate that occurred after stabilization of UC utilization. These findings underscore the potential impact of a checklist on incorporating best practices into daily care of critically ill children.